2015
DOI: 10.5173/ceju.2015.562
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic total extraperitoneal hernia repair during prostatectomy: technique and initial experience

Abstract: IntroductionTo describe the technique of total extraperitoneal inguinal hernia repair performed during Robot-assisted Endoscopic Extraperitoneal Radical Prostatectomy (R-EERPE) and to present the initial outcomes.Material and methods12 patients underwent inguinal hernia repair during 120 R-EERPEs performed between July 2011 and March 2012. All patients had a clinically palpable inguinal hernia preoperatively. The hernia was repaired using a Total Extraperitoneal Patch (TEP) at the end of the procedure.ResultsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In this setting, simultaneous repair of groin hernia can always be repaired quickly and easily. Therefore, groin hernia repair has rapidly gained popularity in the past decade, especially during a robot‐assisted radical prostatectomy, which potentially increases the incidence of groin hernias after surgery . However, whether we really need a surgical robot just for repairing a simple groin hernia is still questionable due to its higher cost, longer operative time, and uncertainty about its clinical benefits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, simultaneous repair of groin hernia can always be repaired quickly and easily. Therefore, groin hernia repair has rapidly gained popularity in the past decade, especially during a robot‐assisted radical prostatectomy, which potentially increases the incidence of groin hernias after surgery . However, whether we really need a surgical robot just for repairing a simple groin hernia is still questionable due to its higher cost, longer operative time, and uncertainty about its clinical benefits …”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic groin hernia repairs are commonly carried out via two standard approaches, either trans‐abdominal pre‐peritoneal (TAPP) repair or total extra‐peritoneal (TEP) repair. In the robotic era, most of the reported robot‐assisted techniques were performed using the TAPP approach, except in very limited case reports of simultaneous TEP repair during a robot‐assisted radical prostatectomy . Although these two standardized laparoscopic approaches for groin hernia repair are comparable in their long‐term clinical outcomes, the TAPP approach was associated with more surgical complications and seroma formation than was the TEP approach in a large‐scale population‐based study …”
Section: Introductionmentioning
confidence: 99%
“…The Urology literature recognizes the relevance of the surgical robot when a TEP is performed at the time of robotic prostatectomy as a combined operation [87]. In the General Surgery literature, where the robotic TAPP approach is favored, the absence of neuralgia after the operation is likely a reflection of all of the advantages offered by the robotic platform in addition to the avoidance of tacks to fix the mesh and close the peritoneal flap, which is similar to the observation made in the ventral hernia series when tacks are avoided as well as transfascial sutures [88].…”
Section: Hernia Repair: From Closing Defects To Suturing Meshmentioning
confidence: 99%
“…Robot‐assisted radical prostatectomy (RARP) for prostate cancer has recently become widespread and is now performed worldwide 1–4 . Although the safety of RARP has been established, the appearance of inguinal hernia (IH) after surgery is one of the late complications of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the safety of RARP has been established, the appearance of inguinal hernia (IH) after surgery is one of the late complications of the procedure. Several studies have reported that patients undergoing RARP have a risk of 4%–20% for developing an IH following this procedure 4–6 . It is speculated that the dissection of the preperitoneal space during radical prostatectomy (RP) can cause contraction of the transversalis fascia, increasing the size of the internal ring and thus causing indirect IH 7 …”
Section: Introductionmentioning
confidence: 99%